1998
DOI: 10.1111/j.1540-8159.1998.tb00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Transiliac Vein Approach to a Permanent Pacemaker Implantation After Aortic Valve Reoperation

Abstract: This article describes the case of a 71-year-old woman in whom a permanent pacemaker implantation was performed through an iliac vein because of superior vena cava obstruction after aortic valve reoperation. During a 6-month follow-up, the patient did well and the pacemaker performance was satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Barakat et al, reported transfemoral pacemaker implantation in three patients in whom pacing via the superior vena cava was not possible or suboptimal [4]. Goto et al, reported transiliac vein approach to a permanent pacemaker implantation, because of superior vena cava obstruction after aortic valve reoperation [5]. Erdogan et al used also transiliac approach in patients who underwent lead extraction for infected pectoral pacemaker systems [6].…”
Section: Discussionmentioning
confidence: 96%
“…Barakat et al, reported transfemoral pacemaker implantation in three patients in whom pacing via the superior vena cava was not possible or suboptimal [4]. Goto et al, reported transiliac vein approach to a permanent pacemaker implantation, because of superior vena cava obstruction after aortic valve reoperation [5]. Erdogan et al used also transiliac approach in patients who underwent lead extraction for infected pectoral pacemaker systems [6].…”
Section: Discussionmentioning
confidence: 96%
“…However, many authors who have described the iliac vein approach expressed concerns about the relation between lead fracture and hip joint movement. 2,4,8,9) It is uncertain whether this complication rate is higher than that for the pectoral approach. Further research is needed to evaluate this complication via the iliac vein approach.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of atrial lead dislodgement using this approach has been reported to range from 7 to 21%. [2][3][4][5] When an atrial lead is implanted using the iliac vein approach, due to anatomical morphology where the atrial lead runs from the external iliac vein to the right atrium via the inferior vena cava, the tip of the implanted atrial lead has to continuously bear its own weight. This gravitydependent force continuously acts on the tip of the implanted atrial lead to withdraw it from the site where it is fixed to the right atrial wall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations